HUBUNGAN MARKETING MIX DENGAN KEPUTUSAN PEMBELIAN KAMAR DI GRAND INNA MUARA HOTEL PADANG - PUTRA, MARDA YOGI; Elida, Elida; Abrian, Youmil (Journal of Home Economics and Tourism, 2014)
This purpose of research to describe the marketing mix, on purchasing decisions rooms, and analyze the relationship between marketing mix with purchasing decisions at the Grand Inna Muara Hotel Padang. This reserach is a descriptive correlational research. The population in this research is the individual guests who stayed at the Grand Hotel Inna Muara Padang amounted to 1787 people with a sample of 95 people. The sampling technique used is incidental sample is a sample technique anyone who by chance met with researchers can be used as a sample, if it is deemed that the person who happened to be found suitable as a source of data. Data collection techniques with a structured questionnaire based on Likert scale that has been tested for validity and reliability. Based on the results of the marketing mix is in the good category (65%), purchasing decisions at the Grand Hotel Inna Muara Padang is in the category fairly (41%). The results showed that there is a Positive and significant relationship marketing mix with the purchase decision in Grand Inna Muara Hotel Padang, it means if marketing mix good, the purchase decision would be good also.Keywords: Marketing Mix and Purchase Decision